2020
DOI: 10.1108/ijefm-12-2019-0061
|View full text |Cite
|
Sign up to set email alerts
|

How the authentic experience of a traditional cultural festival affects the attendee's perception of festival identity and place identity

Abstract: PurposeThis study examines the relationship between authentic experience and festival identity as well as place identity among tourists visiting the 2018 Lugang Dragon Boat Festival, one of the largest traditional cultural festivals in Taiwan and the festival with the longest history.Design/methodology/approachUsing an on-site survey with convenience sampling, a total of 1,360 valid questionnaires were collected in Lugang Township, a well-known, popular heritage tourism destination in Taiwan. The study also ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 86 publications
1
21
0
Order By: Relevance
“…The fact that experience value is highly dependent on both its value proposition and the level of consumer engagement may be perceived as a potential risk from an organizing company's point of view, but as Vargo and Lusch (2008) point out in the perspective of the dominant service logic, the co-creation of value is a central component for constructing positive experiences. This notion, that the perceived value of a festival enhances consumption experiences as satisfaction, is also confirmed by As ¸an et al (2020) and Lin and Lee (2020). It is up to the company to understand the mechanisms that enhance the experience.…”
Section: Practical Implicationssupporting
confidence: 55%
See 1 more Smart Citation
“…The fact that experience value is highly dependent on both its value proposition and the level of consumer engagement may be perceived as a potential risk from an organizing company's point of view, but as Vargo and Lusch (2008) point out in the perspective of the dominant service logic, the co-creation of value is a central component for constructing positive experiences. This notion, that the perceived value of a festival enhances consumption experiences as satisfaction, is also confirmed by As ¸an et al (2020) and Lin and Lee (2020). It is up to the company to understand the mechanisms that enhance the experience.…”
Section: Practical Implicationssupporting
confidence: 55%
“…Relating to perceived value and music festivals, As ¸an et al (2020) examined the mediating effect of perceived festival value on the relationship between satisfaction and experiences, while Oklevik et al (2021) looked at engagement in an event visitor's experience and satisfaction. Lin and Lee (2020) studied the relationship between the authentic experience and festival identity, with value as a mediator.…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical perspective, many scholars have pointed out the significance of convenience as a key precursor to tourist loyalty in festival settings. For example, Lin and Lee [32] confirmed that the convenience of festival activities plays a critical role in improving the quality of theme-based festivals (e.g., cultural festivals). Lee et al [25] also conducted an on-site survey of 500 tourists participating in large-scale international festivals and found that convenient transportation and food quality may affect tourist satisfaction and ultimately their loyalty.…”
Section: Conveniencementioning
confidence: 98%
“…Festivals are conceived of as unique and planned occurrences organised around one or more themes and limited in time and space (Anderton, 2018; Armbrecht et al , 2021). Scholars consider festivals representations of community values, ideologies and identities (Armbrecht et al , 2021; Hall and Page, 2014; Lin and Lee, 2020). When people participate in a festive activity, they are in fact experiencing a place and establishing SOP in the community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So significantly diverse places of the world are casually replaced with anonymous spaces, inviting discussions regarding the place and placelessness, as the debate goes: “place was good, placelessness was not, most things modern were eroding good old places” (Relph, 2016, p. 269). Eventually, the term place-making is utilised as an extended discussion of the place and placelessness to describe the process through which a place derives its identity (Freestone and Liu, 2016; Lew, 2017; Lin and Lee, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%